Cinemática bidimensional da região central das galáxias Seyfert NGC1068 e NGC2110 - Diniz, Marlon Rodrigo (2013)
In this work, we present a two-dimensional mapping of the central region of the active galaxies NGC 1068 and NGC 2110, using near infrared integral field spectroscopy with the instrument NIFS (Near-infrared Integral Field Spectrograph) on the Gemini North Telescope. For NGC1068, we present measurements for the stellar kinematics by fitting the CO absorptions in the H and K bands, at a spatial resolution of 8 pc. For NGC2110 we used K band observations at a spatial resolution of 24pc. Besides the stellar kinematics, we present flux distributions and kinematics for the molecular and ionized gas emission lines. The stellar velocity fields for both galaxies present a typical rotation pattern, being well represented by a kinematic model, in wich the stars have circular orbits in the plane of disk and are subject to a Plummer potential. The mass of the supermassive black hole in the center of NGC1068 was estimated to be M = 4.3+6 −3 × 107M from M −s? relation. For NGC 2110, M was estimated to be M = 1.3+2.5 −0.7 × 108M. The maps for the kinematics and flux distributions of the emitting gas for NGC 2110 were obtained by fitting the H2 l2.1218μm and H I l2.1661μm emission-line profiles by Gauss-Hermite series. The H2 presents extended emission in the whole field of observation, while the Brg is extended only in the southeast northwest direction. The H2 emission is consistent with emission of gas excited by thermal processes, such as gas heated by X-rays from the AGN or shocks. We estimated an excitation temperature of 2100−2700K for H2 emitting gas. The masses of molecular and ionized gas were estimated from fluxes of the H2 l2.1218 and Brg emission lines as MH2 1.4 × 103M and MHII 1.7 × 106M, respectively. The gas velocity fields present a rotation pattern similar to those observed for the stars. In addition, the H2 velocity field presents other kinematic components. Two spiral structures are observed in blueshifts to the north of the nucleus and redshifts to the south of it. If these kinematic structures are originated from emission of gas located in the plane of the galaxy, they can be interpreted as gas flow towards the nucleus (inflow) of the galaxy along the spiral arms. In this case, the mass inflow rate is estimated to be 4 × 10−4M yr−1. Another kinematic component observed for H2 emitting gas was interpreted as ejection of gas from the nucleus (outflow) within a bi-cone with a mass outflow rate of 4.66 × 10−4M yr−1.